Sarah Waters and Contemporary Feminisms
XI, 248 p.
Keywords: This book presents ten readings of Sarah Waters’s fictions published to date in relation to feminism and contemporary feminist theory. The analysis offered in the collection investigates how Waters engages with recent debates on women and gender and how her writings reflect the different concerns of contemporary feminist theories. In particular, the collection includes new and innovative readings of how Waters’s novels address issues of patriarchy, female confinement, madness and misogyny, exploitation and oppression, repression and subordination, abortion, marriage and spinsterhood alongside passionate portrayals of female agency, desire, aesthetics, female sexual expression, and, of course, lesbianism.